2018
DOI: 10.1371/journal.pone.0194790
|View full text |Cite
|
Sign up to set email alerts
|

Novel putative drivers revealed by targeted exome sequencing of advanced solid tumors

Abstract: Next generation sequencing (NGS) is becoming increasingly integrated into oncological practice and clinical research. NGS methods have also provided evidence for clonal evolution of cancers during disease progression and treatment. The number of variants associated with response to specific therapeutic agents keeps increasing. However, the identification of novel driver mutations as opposed to passenger (phenotypically silent or clinically irrelevant) mutations remains a major challenge. We conducted targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…In a study of 44 solid tumors, evidence suggests that new driver mutations included CNVs, indels, and single nucleotide variations (SNVs), and evidence indicated that a small number of mutations sufficed to confer a neoplastic phenotype. These findings underlined the important role driver-gene mutations play in cancer mortality, yet treatment of driver gene mutants with monoclonal antibody was limited in efficacy . In cases where monoclonal antibodies were ineffective against such mutations, ncAAs may be employed to enhance the affinity of the paratope on the antibody toward the epitope on the antigen; incorporate an alkylating side chain into the paratope to construct a covalent paratope-epitope linkage; or reduce the bulky antibody structure to a stabilized loop containing the paratope in order to expedite tighter paratope-epitope interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 44 solid tumors, evidence suggests that new driver mutations included CNVs, indels, and single nucleotide variations (SNVs), and evidence indicated that a small number of mutations sufficed to confer a neoplastic phenotype. These findings underlined the important role driver-gene mutations play in cancer mortality, yet treatment of driver gene mutants with monoclonal antibody was limited in efficacy . In cases where monoclonal antibodies were ineffective against such mutations, ncAAs may be employed to enhance the affinity of the paratope on the antibody toward the epitope on the antigen; incorporate an alkylating side chain into the paratope to construct a covalent paratope-epitope linkage; or reduce the bulky antibody structure to a stabilized loop containing the paratope in order to expedite tighter paratope-epitope interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the prognosis for acute myeloid leukemia has been quite poor, and there have been extensive discussions regarding relapse and post-relapse treatment [ 13 ]. Research using NGS methods has focused on identifying driver mutations and understanding how clonal evolution progresses based on these drivers [ 14 ]. Recent studies have suggested the existence of linear evolution and branching evolution when specific AML clones survive during remission to later contribute to relapse [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of a tumor’s genetic profile is crucial to improve clinical-decision making in the patient management. Consequently, laboratories must integrate high-throughput sequencing technologies in routine molecular diagnostics [3]. These allow the simultaneous testing of multiple genetic alterations (point mutations, insertions, deletions, copy number variations and translocations) and quantify molecular subclones by procedures that provide accurate, reliable and cost-effective results.…”
Section: Introductionmentioning
confidence: 99%